Measuring the Effect of Retail Store Promotions on Brand and Store Substitution - Kumar, V.; Leone, Robert P. (Journal of Marketing Research, 1988)
Using store-level scanner data, the authors investigate the effect of retail store price promotion, featuring, and displays on sales of brands of disposable diapers within a city. A hierarchical, cross-sectional, and time-series modeling procedure is used to identify the competitive structure among retail stores within a test market city. Models are developed for pooled store pairs to investigate the effect of promotion on store substitution. The specification of these models is based on findings from within-store brand substitution models. Within a store, price promotion produced the largest amount of brand substitution, followed by featuring and displays. Similarly, these activities produced store substitution in certain instances. However, which specific promotional variables are significant and the magnitude of the effect are a function of the geographic proximity of the stores.